The enabling factors for green building development of housing projects in Malaysian / Nur Atifah Bahruddin - Bahruddin, Nur Atifah (2019)
Transformation of the housing industry in Malaysia deliver huge benefits to accelerate Malaysian economic growth, but it requires a lot of involvement and efforts from various parties to implement. Here, the transformation of green housing also is able to preserve natural environment by fulfilling the quality of lifestyle of homeowners. Green housing is designed as sustainable manner with maximizing the resources and produces less impact on the environment. Furthermore, the Malaysian government had shown interest and encourages the practice of green development by various green policies and green rating measures. Through the National Green Technology Policy, the Malaysian government has the provision of housing should be developed in a sustainable manner in order to encourage green practice in the housing industry. Plus, the introduction of Green Building Index (GBI) as green rating tool for buildings to promote sustainability and growing awareness among construction players. However, the implementation of green housing is quite low due facing barriers to be implemented such as, budget constraints, lack of knowledge and information and lack of enforcement by government. Therefore, this research is focusing on to explore the issues implementation of green housing projects by looks in detail on the enabling factors being considered in green housing projects.